The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22541/au.160356605.51956306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The methylome of Biomphalaria glabrata and other mollusks: enduring modification of epigenetic landscape and phenotypic traits by a new DNA methylation inhibitor

Abstract: 5-methylcytosine (5mC) is an important epigenetic mark in eukaryotes. Little information about its role exists for invertebrates. How 5mC contributes to phenotypic variation in invertebrates can be investigated by experimental alteration of methylation patterns. Here, we apply new non-nucleoside DNA methyltransferase inhibitors (DNMTi) to introduce global changes into the methylome of mollusk species. Flavanone inhibitor Flv1 was highly efficient in reducing 5mC in the freshwater snails Biomphalaria glabrata a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Furthermore, we previously demonstrated that DNA methyltransferase (DNMT) inhibitors induce phenotypic diversity in the morphometric traits of treated B. glabrata snails and its offspring (Luviano et al, 2021). We also showed that DNA methylation is essential for the snail (Luviano et al, 2023). Both, the existing knowledge on DNA methylation and phenotypic responsiveness to infestation make B. glabrata snails are an ideal system to study the role of DNA methylation in the generation of phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, we previously demonstrated that DNA methyltransferase (DNMT) inhibitors induce phenotypic diversity in the morphometric traits of treated B. glabrata snails and its offspring (Luviano et al, 2021). We also showed that DNA methylation is essential for the snail (Luviano et al, 2023). Both, the existing knowledge on DNA methylation and phenotypic responsiveness to infestation make B. glabrata snails are an ideal system to study the role of DNA methylation in the generation of phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 78%
“…The pipeline is available at: . The filtered and demultiplexed reads from epiGBS2 pipeline were used in another pipeline adapted from previous work [ 33 ], using the Galaxy project server as applied in [ 34 ]. Adapter removing was done using TrimGalore!…”
Section: Methodsmentioning
confidence: 99%